THE INFLUENCE OF SERVICE QUALITY AND PRICE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE IN ONLINE TRANSPORTATION GRABBIKE (Study on Management Students at Makassar State University) - Uhud Darmawan Natsir; Juliyati, Nurul Fadilah Aswar, Chalid Imran Musa, Muhammad Ilham Wardhana Haeruddin, Muhammad Said (CV. Adiba Aisha Amira, 2025)
The purpose of this study was to determine the effect of service quality and price on customer loyalty through customer satisfaction as an intervening variable in Grabbike online transportation (for management students, Makassar State University). The sample used was 100 Grabbike customers who had been selected based on predetermined criteria. The data analysis technique was carried out by questionnaire, observation and literature study. The data analysis technique used in this study uses SmartPLS version 3. Based on the results of the study, it shows that the service quality variable has a positive and significant effect on customer loyalty. Service quality variables have a positive and significant effect on customer satisfaction. The price variable has a positive but insignificant effect on customer loyalty. The price variable has a positive and significant effect on customer satisfaction. The customer satisfaction variable has a positive and significant effect on customer loyalty. Service quality variables have a positive and significant effect on customer loyalty through customer satisfaction. The price variable has a positive and significant effect on customer loyalty through customer satisfaction.